2019
DOI: 10.1039/c8sc03385d
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing nickel-rich layered oxide cathodes by magnesium doping for rechargeable lithium-ion batteries

Abstract: Magnesium doping in a high-capacity Ni-rich cathode suppresses cation mixing and transition-metal migration, leading to remarkable structural stability and cycling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(125 citation statements)
references
References 55 publications
(24 reference statements)
2
119
0
Order By: Relevance
“…Among others, it was demonstrated that especially the properties of Ni-rich NCMs show strong correlations with those of LiNiO 2 (e.g., in terms of crystallographic changes and phase transformation behavior, eventually leading to material fatigue). [238] Improvements in performance can also be achieved by anionic fluorine doping. Future research should clearly be focused on enhancing the electronic stability of materials to better protect them from, e.g., lattice oxygen loss.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Among others, it was demonstrated that especially the properties of Ni-rich NCMs show strong correlations with those of LiNiO 2 (e.g., in terms of crystallographic changes and phase transformation behavior, eventually leading to material fatigue). [238] Improvements in performance can also be achieved by anionic fluorine doping. Future research should clearly be focused on enhancing the electronic stability of materials to better protect them from, e.g., lattice oxygen loss.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…It's well-known that the specic surface area, pore diameter, and pore volume all inuence the electrochemical performance of the active electrode materials. [58][59][60] The specic surface area and pore size distribution of the synthesized (Mg 0.2 Ti 0.2 Zn 0.2 Cu 0.2 Fe 0.2 ) 3 O 4 particles were measured via nitrogen adsorption-desorption isotherm analysis ( Fig. S2(a) †).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Rechargeable lithium-ion batteries (LIBs), as one of the energy storage technologies, are the key part of the contemporary energy system which is closely coupled with renewable energy generation, transmission and utilization [1][2][3][4]. Meanwhile, due to the high energy density, long lifespan and environmental friendliness, LIBs have been highly developed over the past decades and widely used in our daily life including portable electronics, electrical transportation, and even grid energy storage [5][6][7]. However, the current most mature LIBs cannot ever meet the ever-increasing demands [8][9].…”
Section: Introductionmentioning
confidence: 99%